Options Payoffs Perspective on Financial Engineering - Muli, Charles N. (Machakos University, 2018)
The option theory and its applications play an important role in modern finance. Many trading strategies, corporate incentive plans, and hedging strategies include various types of options. In this paper, the option definitions and basics of how the instruments are traded will not be the main focus but in particular, we will focus on the critical aspects of the dynamics of payoff and profit/loss functions, the difference between European versus American options, the Binomial option model with/without dividends, and different trading strategies.